Imaging ocean surface statistics using Geosynchronous Correlating SAR (CoSAR) - López-Dekker, Paco; Rodríguez-Cassola, Marc; De Zan, Francesco; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2014)
This paper discusses a novel radar imaging concept called a Correlating SAR (CoSAR) and its application to the observation of the second order statistics of the radar echoes corresponding to the ocean surface. It is shown that these statistics can be retrieved by jointly processing the radar echoes received by two radars that have a relative motion.
DLR Import::2019-04-03